Effects of rubber seed meal on the performance of mature chicken - Rajaguru A S B
Investigation on the effects of rubber seed meal in maturity of pullets, egg production, egg size, shell quality, hatchability, livability of chicks hatched out and semen quality of the cocks were carried out. The pullets that were raised on 10;, 20;,30;and 40;rubber seed meal in diets from the third month of age matured late, but the egg production was normal. However, the increase of rubber seed meal in diets lowered egg size, shell thickness, hatchability of incubated eggs and the weight of the chicks hatched out. It was also observed that the rubber seed meal increases the percentage of infertile eggs that were produced. The R.S.M had no effect on the quality of semen of the cocks used for artificial insemination. these effects may be due to an amino acid imbalance of R.S.M that lowers the biological value of proteins in diets and the prescence of an antifertility factor which has not been identified yet. The results indicated that R.S.M should not be used in breeder rations. In layer rations, it could eb used only up to 20;level.
Keywords: Mature chicken; Rubber seed meal